Urine glucose concentration: A useful parameter as a surrogate for glycaemia on the first day of life in canine neonates. (December 2020) - Molina, Carla; Bosch, Luis; Rigau, Teresa; Yeste, Marc; Torrente, Carlos; Rivera del Alamo, Maria Montserrat
Abstract: Introduction: Hypoglycaemia is a well-known risk factor in neonatal puppies and kittens; glycaemia control is crucial during the first days of life. Kidneys immaturity provokes the presence of physiological glycosuria during the first 2–3 weeks of life in small animals. Objectives: The aim of this study was to evaluate the potential of glycosuria as a predictor of glycaemia in neonatal puppies during the first two weeks of life. Methods: Prospective study. Thirty-three client-owned healthy neonatal puppies admitted to the Veterinary Teaching Hospital, Autonomous University of Barcelona, were included in the study and divided into four different groups according to the day of sampling (1, 4, 7, and 11 days post-delivery). Glucose levels in blood and urine samples were evaluated and compared between groups. Correlation between glucose levels in blood and urine was also determined. Results: Hypoglycaemia was diagnosed in 17.14% of the puppies and only on day 1 after delivery. A positive and significant correlation between blood and urine glucose concentration on day 1 after delivery was observed. No significant correlation between blood and urine glucose was observed on days 4, 7 and 11 after delivery. Conclusions: Urine concentration of glucose is a useful parameter to establish glycaemic status on the first day of life in canine puppies. Highlights: A positive and significant correlation between blood and urine glucose concentration on day 1 after delivery was observed. No correlation between blood and urine concentration was observed in puppies older than 1 day of life. Urine glucose concentration is a useful tool to determine the presence of hypoglycaemia in 1-day old puppies.